THE INFLUENCE OF CONSUMER RETENTION AND ANALYSIS OF SERVICE QUALITY TOWARDS ONLINE SHOPPING AT ENTERKOMPUTER.COM - Lala, Eirikta Jeisen (Sam Ratulangi University, 2016)
Online buying and selling has become an important part of many people's lives. Students and parents rely on the internet to acquire and sell textbooks at affordable prices, virtual stores allow people to shop from the comfort of their homes without the pressure of a salesperson, and online marketplaces provide a new and more convenient venue for the exchange of virtually all types of goods and services. Both businesses and customers have embraced online sales as a cheaper and more convenient way to shop, but just like anything associated with the internet, there are benefits and dangers associated with shopping online. In the other words, society need to learn more about the technology especially the internet and always be aware to surf it as well. So as the first step, people should afford electronic devices such as smartphone, laptop, or a personal computer in order to be able to do an online buying or selling activity. Therefore this Thesis has been made to analyze and give explanations about how well Consumer Retention and Service Quality influencing an Online shopping behavior towards one of the well-known and most trusted online webstore Enterkomputer.com that provides many electronic devices especially computer stuffs and peripherals that located at Mangga 2 Mall, second floor, C block No 101-106, Jakarta Pusat.